2014
DOI: 10.1159/000358641
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Frequency Dependence of Action Potential Duration and the Expression of TRPC3 in Rabbit Ventricular Myocardium

Abstract: Background/Aims: Cardiac action potential duration (APD) is regulated by heart rate, leading to the trans-membrane movement of inorganic ions. Whether the alteration of heart rate can affect the expression of transient receptor potential canonical channels (TRPCs), further studies should be made. We investigated the changes of APD at different stimulus frequencies and their influences on the expression of TRPCs in rabbit ventricular myocardium. Methods: Monophasic action potential (MAP) was recorded by contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Based on this observation we investigated the impact of alternating excitation directions on intrinsic FP features and identified significant differences. However, different beating rates lead to electrophysiological changes such as alteration of AP duration or upstroke velocity (29,42,51). To exclude beating-rate-induced effects, an analysis of the changes of the beating rate among competitive endogenous active pacemakers was performed showing, interestingly, almost similar frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this observation we investigated the impact of alternating excitation directions on intrinsic FP features and identified significant differences. However, different beating rates lead to electrophysiological changes such as alteration of AP duration or upstroke velocity (29,42,51). To exclude beating-rate-induced effects, an analysis of the changes of the beating rate among competitive endogenous active pacemakers was performed showing, interestingly, almost similar frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that chemerin protein caused no alteration in the Na + channel current during phase 0. On the other hand, MAP90 provides information about the repolarization phase of AP; it is inversely proportional to the number of heartbeats (30). The MAP90 showed a statistically insignificant change in the chemerin-treated groups compared with the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MAPamp is formed due to the diffusion of Na + ions into the cell via voltage-gated Na + channels during the first phase of MAP (39). MAP 90 is inversely proportional to heart beats, and MAP duration is affected by the balance between inward depolarizing and outward repolarizing currents in the myocytes (40, 41). Our findings suggest that omentin does not influence these currents.…”
Section: Discussionmentioning
confidence: 99%